Improving Performance by Embedding HPC Applications in Lightweight Xen Domains - Thibault, Samuel; Deegan, Tim (2nd HPCVIRT, 2008)
Although they allow easy and cost-effective use of a wide range of machines, the programming interface and behavior of general-purpose Operating Systems (OS) often fail to meet, or even conflict with, the specific desires of High-Performance Computing (HPC) applications, such as low preemption or control over memory and I/O management. That often leads to poor performance. On the other hand, hypervisors are more and more commonly used on top of those OSes for various reasons, such as ease of dedicated environment deployment or load balancing. In contrast to the usual unix process model, hypervisors provide their guests with kernel-level facilities. In this paper, we show how an HPC application and its execution environment can be embedded within a lightweight guest domain, alongside a domain that runs a conventional OS which is only used for administrative purpose. That permits the execution environment to take advantage of kernel-level facilities to improve performance, which would be hard to achieve in the traditional process model because of lack of support or excessive overhead.